PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA DI KELAS VI SDN INDRASARI 2 MARTAPURA MELALUI PENDEKATAN LINGKUNGAN - fahrudi fahrudi (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
Abstract: This study aims to improve learning activities and student learning outcomes on plant propagation material through an environmental approach. This research is a classroom action research (CAR). The research design used in this study is the Classroom Action Research (CAR) model, as many as 2 cycles, consisting of the steps of Planning / Preparation, Implementation (Action), Observation and Reflection. The results of reflection will be the basis for the next cycle. The research subjects in this study were students of class VI A SDN Indrasari 2 Martapura, amounting to 21 people. Data was extracted and collected from observation sheets on learning activities and student learning outcomes tests at the end of the action at each meeting. Data analysis techniques use averages and percentages. The results of this class action research show increased learning activities and learning outcomes of students of class VI A SDN Indrasari 2 Martapura on plant propagation material through environmental approaches increases and is classically complete..